2010
DOI: 10.1590/s1677-55382010000100006
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ureteral reimplant for ureteral stricture

Abstract: Purpose: Evaluate the initial experience of laparoscopic ureteral reimplant for ureteral stenosis. Materials and Methods: From January 2004 to June 2008, 10 patients underwent 11 laparoscopic reconstruction surgeries for ureteral stenosis. Seven cases of stenosis of the distal ureter, two at the level of iliac vessels, a case of bilateral distal stenosis and one in the medium third. Eight ureteroneocystotomies were performed by extravesical technique with antireflux mechanism, two cases of vesical reimplant wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
2
12
0
1
Order By: Relevance
“…1 Recently, the laparoscopic (LAP) approach to the UNC has been described in several reports. [2][3][4] Such series hail excellent success rates proving feasibility without comparison. One report, a matched cohort of 10 patients, revealed demonstrable improvements in estimated blood loss (EBL), morphine requirements, length of stay (LOS), and convalescence time 5 when compared to open UNC.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, the laparoscopic (LAP) approach to the UNC has been described in several reports. [2][3][4] Such series hail excellent success rates proving feasibility without comparison. One report, a matched cohort of 10 patients, revealed demonstrable improvements in estimated blood loss (EBL), morphine requirements, length of stay (LOS), and convalescence time 5 when compared to open UNC.…”
Section: Introductionmentioning
confidence: 99%
“…[3,[6][7][8][9][10][11][12][13][14][15][16][17] Rassweiler et al [7] observed longer operative time (253 minutes vs. 220 minutes), shorter hospital stay (8 days vs.17 day) with 100% successs rate in the [11] 1 210 3 90 50 mg morphine…”
Section: Discussionmentioning
confidence: 99%
“…Ramalingam et al [8] Allarpathi et al [15] 2 RALBF UT 1 M 2R 245 2 30 6 22 mg morphine 1F Soares et al [16] 2 H 2F 1R US 1L 120 2 140 6 Gozen et al Ramalingam et al [8] performed laparoscopic ureteral reimplantation with Boari flap in 3 patients successfully with median operative time of 320 mins (range 300-320 min). Castillo et al [9] reported 9 cases of laparoscopic reimplantation procedure with Boari flap.…”
Section: Discussionmentioning
confidence: 99%
“…Para lesiones de uréter medio y distal, sobretodo de gran longitud, la técnica de neoimplante de fl ap Boari permite confeccionar una anastomosis libre de tensión entre el uréter y el fl ap vesical. Si bien el estándar continúa siendo la cirugía abierta, desde que esta técnica fue inicialmente descrita por vía laparoscópica en modelos animales 11 , existen varias series publicadas en la literatura en el manejo de patologías ureterales benignas con resultados alentadores comparables a su contraparte abierta 4,5,[12][13][14][15] . Sin embargo, en lo que se refi ere a patología oncológica, sólo se han publicado 2 casos en la literatura reciente 5,6 .…”
Section: Discussionunclassified